Non-Polar Chain-Enabled Suspension of Carbon Nanoparticles in Base Oil - M. Humaun Kabir; Darrius Dias; Evan Johnson; Joe Kosmoski; Hong Liang (Lubricants)
The transition to electric vehicles (EVs) has introduced new challenges in lubrication, demanding innovative solutions to ensure consistent performance. One promising approach is the use of nanoparticle additives, which have the potential to improve lubrication performance significantly. However, achieving a stable suspension of these nanoparticles in lubricating oils remains a critical challenge, as suspension stability is essential for maintaining consistent performance and maximizing the benefits of these advanced additives. In this study, carbon nanoparticles (CNPs) were modified with dodecylamine (DDA) to achieve stable suspension in nonpolar fluids. The successful functionalization was confirmed by the FTIR results, which showed characteristic peaks of various bonding. The suspension stability tests demonstrated that DDA-CNPs remained suspended for over 60 days in the Polyalphaolefin (PAO) oil, whereas unmodified CNPs were sedimented within 3–7 days. The rheological behavior was measured under different shear rates and temperatures. Viscosity measurements indicated that DDA-CNPs maintained a lower value compared to base PAO. The lubricants’ friction coefficient (COF) was also determined under various speeds and loads. The addition of DDA-CNPs at a concentration of 0.05 wt.% resulted in a significant reduction in COF, with values decreasing by 26% compared to base PAO oil under a load of 1 N. Additionally, the COF for DDA-CNPs was consistently lower than that of PAO, with reductions ranging from 15% to 18% across all tested speeds. The Stribeck curve further highlighted the improved performance of DDA-CNPs across boundary, mixed, and hydrodynamic lubrication regimes. These findings suggest that DDA-CNPs significantly improve the lubrication performance of PAO oil, making them suitable for advanced lubrication applications in automotive and industrial systems.